Tom Clancy oath of office - Cameron, Marc (G.P. Putnam's Sons, 2018)
Marine officer. CIA analyst. President. Jack Ryan has devoted his life to protecting the United States. What if this time, he can't? President Ryan and the Campus return in the latest entry in Tom Clancy's #1 New York Times-bestselling series.